2015
DOI: 10.1007/s12032-015-0678-8
|View full text |Cite
|
Sign up to set email alerts
|

Screening of multi-targeted natural compounds for receptor tyrosine kinases inhibitors and biological evaluation on cancer cell lines, in silico and in vitro

Abstract: Receptors for growth factors encompass within the superfamily of receptor tyrosine kinases and are known to regulate numerous biological processes including cellular growth, proliferation, metabolism, survival, cell differentiation and apoptosis. These receptors have recently caught the attention of the researchers as an attractive target to combat cancer owing to the evidence suggesting their over-expression in cancer cells. Therefore, we studied receptor-based molecular docking of IR (PDB; 3ETA), IGF1R (PDB;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 50 publications
(57 reference statements)
0
10
0
Order By: Relevance
“…However, the mechanism that leads to ubiquitinized Akt is still unknown. Recent studies reported that multiple growth factor receptors such as EGFR and insulin-like growth factor 1 receptor, might be possible targets of natural compounds (55,56). Since the ubiquitination-proteasomal degradation of intracellular proteins is modulated by the downstream signaling of these receptors (57)(58)(59)(60), it is possible that the mechanism of vanillin action on ubiquitinized Akt might involve vanillin-modulating of these receptors and their signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism that leads to ubiquitinized Akt is still unknown. Recent studies reported that multiple growth factor receptors such as EGFR and insulin-like growth factor 1 receptor, might be possible targets of natural compounds (55,56). Since the ubiquitination-proteasomal degradation of intracellular proteins is modulated by the downstream signaling of these receptors (57)(58)(59)(60), it is possible that the mechanism of vanillin action on ubiquitinized Akt might involve vanillin-modulating of these receptors and their signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…EGCG reduced cell proliferation and ROS generation. EGCG also reduced cell migration, suggesting its anti-metastasis activity [ 58 ].…”
Section: Computational Mdamentioning
confidence: 99%
“…In addition to the above-mentioned studies, we have discussed the results of CMDA related to the interaction of EGCG with cancer-related proteins [ 5 ], including glucose regulated protein-78 [ 42 ], insulin-like growth factor-1 receptor [ 43 ], vascular endothelial growth factor (VEGF), VEGF1-receptor and VEGF2-receptor [ 44 ], zeta chain of T cell receptor associated protein kinase 70 [ 45 ], tyrosine kinases [ 46 ], tumor necrosis factor (TNF) receptor associated factor 6 (TRAF6) [ 47 ], urokinase [ 48 ], chymotrypsin [ 49 ], lipase [ 50 ], hydroxymethylglutaryl CoA reductase [ 51 ], leukotriene A4 hydrolase [ 52 ], DNA methyltransferase [ 53 ], phosphoinositide-3-kinase [ 54 ], protein phosphatases [ 55 ], and signal transducer and activator of transcription 3 (STAT3) [ 56 ].…”
Section: Cmda Of Catechin-protein Interactionmentioning
confidence: 99%